2022
DOI: 10.1177/19322968221103610
|View full text |Cite
|
Sign up to set email alerts
|

Remote Research: Resources, Intervention Needs, and Methods in People with Diabetes and Peripheral Neuropathy

Abstract: Background: Stay-at-home orders associated with the SARS-CoV-2 (COVID-19) pandemic were particularly important for older adults with type 2 diabetes, at risk for severe COVID-19 complications. In response, research shifted to remote telehealth methodology. Study participant interests, equipment needs, and ability to adapt methods to the remote/telehealth environment were unknown. Study purposes to assess (1) resource needs (internet/devices accessibility), (2) future telehealth interests, and (3) ability to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The second study Sunil Kumar et al , (2020) was carried out in India with total of 300 patients and an age of patients with DM from 18 -65 years, intervention group given using diabetes mobile during 6 months and control group with standard care, instrument used to measure the outcomes is WHO QOL BREF questionnaire, and outcomes from the research is the differences in the change in scores of quality of life of participants recruited in intervention and non-intervention groups were statistically significant in all the four domains after the intervention with a p value < 0.001 (Sunil Kumar et al, 2020) The third study Bohnert et al, (2023) was carried out in USA with total of 21 respondents an age 66 years, intervention group given using zoom application and intervention given to 5 months and control group with standard care, instrument used to Measurement Information System (PROMIS), and outcomes from research is showed that all participants completed the survey well via the zoom application, and participants reported minimal levels of depression and good QoL (anxiety: Adams = 49.1 ± 7.2, Bohnert = 48.2 ± 7.4, depression: Adams = 48.3 ± 8.2, Bohnert = 48.9 ± 7.6, and fatigue: Adams = 50.9 ± 8.5, Bohnert = 50.8 ± 8.4) (Bohnert et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The second study Sunil Kumar et al , (2020) was carried out in India with total of 300 patients and an age of patients with DM from 18 -65 years, intervention group given using diabetes mobile during 6 months and control group with standard care, instrument used to measure the outcomes is WHO QOL BREF questionnaire, and outcomes from the research is the differences in the change in scores of quality of life of participants recruited in intervention and non-intervention groups were statistically significant in all the four domains after the intervention with a p value < 0.001 (Sunil Kumar et al, 2020) The third study Bohnert et al, (2023) was carried out in USA with total of 21 respondents an age 66 years, intervention group given using zoom application and intervention given to 5 months and control group with standard care, instrument used to Measurement Information System (PROMIS), and outcomes from research is showed that all participants completed the survey well via the zoom application, and participants reported minimal levels of depression and good QoL (anxiety: Adams = 49.1 ± 7.2, Bohnert = 48.2 ± 7.4, depression: Adams = 48.3 ± 8.2, Bohnert = 48.9 ± 7.6, and fatigue: Adams = 50.9 ± 8.5, Bohnert = 50.8 ± 8.4) (Bohnert et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This finding may be related to the coexistence of multiple chronic diseases (Skou et al, 2022), which results in increased needs and the inability of telenursing to meet those needs (Janjua et al, 2021), a circumstance in which face‐to‐face care services may be more beneficial. Relevant studies have shown (Bohnert et al, 2022) that the need for home‐based care for diabetes primarily focuses on knowledge related to complications, and that for older adults with T2DM, relevant technical support is necessary to complete telemedicine activities. However, these needs cannot be met due to the imbalance of medical resources or objective factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that, although self-management is effective in changing the cognition of people with T2DM, contributing to behavioral change and emotional perception, the maintenance of these behaviors still seems to be insufficient in the long term; therefore, an approach with individuals who have been diagnosed for longer is also essential, as it ensures continuity of care, reduces the possibility of chronic complications such as neuropathy, retinopathy, renal and neurological damage (25,42).…”
Section: Evidence Summarymentioning
confidence: 99%